(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Coronavirus disease (COVID-19) outbreak, caused by the most recently discovered coronavirus, is currently affecting a large population across the globe. World health organization (WHO) has already declared COVID-19, a pandemic, and the world is fighting to contain the COVID-19 outbreak. Nepal has taken several preventive measures to control the coronavirus outbreak. However, some additional steps are needed to prevent community transmission of the disease. This brief communication discusses the government of Nepal actions and provides recommendations for the prevention and control of COVID-19 infection in Nepal.